Implementasi Strategi Master dalam Pembelajaran PAI secara Daring - Muhammad Sya’roni (Cendekia, 2021)
The education is feeling the impact of the Covid-19 Pandemic until now,. Learning in schools must be carried out in a mixed manner, online and offline. This was meant to minimize the spread of the corona virus and to continue the educational process. It is recognized that the quality of online learning is not as good as offline learning. For this reason, it is necessary to innovate online Islamic Education learning. This research is a library research. The approach model used is a Content Analysis approach, this research is in-depth discussion of the MASTER strategy and its implementation in online PAI learning. The results showed that the implementation of the MASTER Strategy in online Islamic Education learning can be implemented in 6 steps which include: (1) Motivating students' minds; (2) directing students to understand the learning material; (3) inviting students to investigate meaning; (4) triggering the memory of students; (5) asking students to show what was known; (6) inviting students to reflect on the learning process.